Rubella seroprevalence among first-grade primary school students in a district in Istanbul, Turkey - TOPUZOĞLU, AHMET; AY, NADİYE PINAR (W B SAUNDERS CO LTD, 2006)
Objectives Rubella vaccination is not included in the national immunization programme of Turkey. However, it is on the market and is recommended, mainly by the private sector, at the age of 12-15 months. Introduction of the rubella vaccine without achieving high coverage has the risk of shifting the mean age of rubella infection among the unvaccinated population to reproductive ages. The aim of this study was to evaluate the seroprevalance of rubella and the factors associated with seropositivity among primary school students in Umraniye, a district of Istanbul. Methods: Blood samples were collected from 489 students in 70 primary schools of Umraniye. Parents completed a concise questionnaire assessing sociodemographic characteristics and measles, mumps and rubella vaccination status. Results: Among the students screened, 163 (33.3%, 95% confidence intervals 29.2-37.7%) were susceptible to rubella. When sociodemographic variables were evaluated, paternal education was the only variable associated with seronegativity. As the level. of paternal education increased, seronegativity rates decreased. This finding may suggest that rubella vaccination is practiced more commonly among children whose fathers are better educated. Conclusions: Surveillance and control of rubella and congenital rubella syndrome must be set as public health priorities in Turkey, particularly given that rubella vaccination is practiced partially in the country. (c) 2005 The Royal Institute of Public Health. Published by Elsevier Ltd. All rights reserved.
Keywords: rubella; seroprevalance; students; Turkey; UNVACCINATED POPULATION; RISK-FACTORS; CHILDREN; VACCINATION; SCHOOLCHILDREN; IMMUNIZATION; PREVALENCE; COVERAGE